Changes in Intraocular Pressure and Angle Status After Phacoemulsification in Primary Angle Closure Hypertension. Issue 2 (February 2019) - Selvan, Harathy; Angmo, Dewang; Tomar, Ankit S.; Yadav, Suresh; Sharma, Arpit; Dada, Tanuj
Abstract : Purpose: To study the change in intraocular pressure (IOP) and angle status after phacoemulsification in a cohort of primary angle closure hypertension (PACHT) patients. Setting: Tertiary Eye Care, India. Design: Prospective interventional case-series. Methods: Case-series of 18 eyes of 18 patients. Preoperative biometry including axial length, anterior chamber depth (ACD), lens thickness, and central corneal thickness were studied. Preoperative and postoperative IOP, number of topical glaucoma medications, angle swept source optical coherence tomography (SS-OCT) parameters of nasal and temporal angle opening distance, trabecular iris space area, scleral spur angle, lens vault and circumferential iridotrabecular contact (ITC) were studied and their correlations derived. Results: The mean preoperative IOP, 31±6 mm Hg, decreased to 14±1 mm Hg at 6-months postoperative period, P <0.001, a fall by 58±14%. The number of glaucoma medications reduced from 4(3-5) to 2(1-3), P <0.001. All SS-OCT studied parameters denoted significant angle widening postsurgery. The ITC% reduced from 52(16-100) to 19(0-97), P <0.001. The preoperative ITC showed moderate to strong correlation with all preoperative nasal and temporal angle parameters. It also showed moderate positive correlation with percentage fall in IOP at 1-month postoperative period. The preoperative ACD showed significant negative correlation with preoperative and postoperative ITC. Conclusions: PACHT patients benefit significantly from cataract surgery with marked angle widening, IOP reduction and a decrease in the number of glaucoma medications. The SS-OCT derived circumferential iridotrabecular contact index can be used as the single best parameter to indicate the preoperative angle status and predict postoperative change in IOP, as against the numerous single section measured angle parameters.